Model of the Development of Creative Abilities of the Future Teachers of Primary Classes in the Process of Art-labor Training - Alla Hryhorieva (Pedagogical Discourse, 2018)
The article focuses on redefining the paradigm of education. It is noted that the new Ukrainian school should ensure the comprehensive development of the individuality of person as a personality and the highest value of society on the basis of identifying his or her inclinations, abilities, gifts and talents. The central figure in the modernization of the educational process is the teacher of the new formation – the researcher-pedagogue, a creative personality, a professional whose characteristic features are modern scientific and pedagogical thinking, high spirituality, intelligence, optimism, constant readiness for self-education, self-development. Therefore, special attention requires the formation of the creative personality of the teacher, his or her professionalism. It is mentioned that a special place in the formation of the creative personality of the future teacher of primary classes belongs to the disciplines of artistic and labor orientation, the purpose of which is: development of the ability of students to fully perceive the phenomena of art, social life, nature; formation of creative thinking, aesthetic tastes, expansion of world outlook in the field of artistic and folk culture, knowledge deepening; development of interest to the beauty in the environment; perfection of moral, aesthetic needs and interests of youth, their aesthetic orientations, analysis of artistic works; development of emotionality, sensory-ideological attitude of students to the environment in all its manifestations; activating creative self-expression of students.The essence of the concept «model of development of creative abilities of the future teachers of primary classes in the process of artistic-labor training» has been highlighted. The author’s model of the mentioned preparation has been offered. The attention is focused on the main blocks of the model: target, theoretical-methodological, content, organizational-procedural, evaluation-diagnostic, effective. The pedagogical conditions of development of creative abilities of the future teachers of primary school in the process of artistic-labor training have been determined, among them: creation of problem-solving situations and creative tasks; use of project technology training; optimal combination of educational and extra-curricular work on the basis of creative interaction. It is noted that pedagogical conditions are effectively realized through the following methods, forms, means of development of creative abilities: integrated lectures, seminars-discussions, role games, project activity of students (creative projects and their demonstration, drawing up of a portfolio), competition-exhibition work (festivals, exhibitions, contests, installations, social projects), reflexive exercises (compositions-reflections, reflexive essays, sketches), independent research activity of students (analysis of scientific sources, analysis of practical experience, reviews). The conclusion is made on the integrity, step-by-step and dynamism of the author’s model; the possibility of integrating the developed system into existing conditions of higher education.